The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/0954406214525771
|View full text |Cite
|
Sign up to set email alerts
|

Study of coating's effects on mechanical performances for sleeve of cotton picker with fluid–structure interaction method

Abstract: A sleeve and its matched spindle are key components of a cotton picker, whose performances affect picking cotton efficiency directly. To enhance the sleeve strength and wear resistance, it is desired to add coatings on the inner surface of the sleeve. In this paper, influences of the coatings on the mechanical performances of the sleeve are investigated with fluid-structure interaction method. Mechanical performances of the sleeve are studied at the varied elastic modulus, Poisson's ratio, and thickness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…For this investigation, the hardness, elastic modulus and Poisson's ratio of the nick coating used are 540 HV, 69 GPa and 0.31, respectively, whose original surface morphology is shown in Figure 2. The elastic modulus and Poisson's ratio of the grinding ball are the same as the corresponding values of the sleeve, which are 200 GPa and 0.3, respectively (Meng and Chen, 2014). To keep the specimen lubricated fully with the lubricant, its lubrication state should be evaluated before the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this investigation, the hardness, elastic modulus and Poisson's ratio of the nick coating used are 540 HV, 69 GPa and 0.31, respectively, whose original surface morphology is shown in Figure 2. The elastic modulus and Poisson's ratio of the grinding ball are the same as the corresponding values of the sleeve, which are 200 GPa and 0.3, respectively (Meng and Chen, 2014). To keep the specimen lubricated fully with the lubricant, its lubrication state should be evaluated before the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…However, little work open is involved in the coating effect on tribological performances for the spindle. Recently, a fluid-structure interaction method was used by the first author to explore stress characteristics of the coated spindle (Meng and Chen, 2014). To reduce the spindle's friction and increase its wear resistance, the effect of the hard chrome coating, as one kind of hard coating, on the spindle was studied by the first author (Meng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Since the variation of the friction coefficient under the oil lubrication tends to be consistent with ones of the stress and deformation of the coated surface, the above mechanism rule for the hard chromium coating also validates the previous work from the authors, in which we found that the stress and deformation on the inner surface of the lubricated bearing become smaller with increasing h c within a certain thickness range. 13…”
Section: Resultsmentioning
confidence: 99%
“…Since the variation of the friction coefficient under the oil lubrication tends to be consistent with ones of the stress and deformation of the coated surface, the above mechanism rule for the hard chromium coating also validates the previous work from the authors, in which we found that the stress and deformation on the inner surface of the lubricated bearing become smaller with increasing h c within a certain thickness range. 13 Additionally, it can be found from Figure 7 that at the same h c , the friction coefficient in the dry sliding condition is larger than that of the oil lubrication condition, indicating that conclusions about the coating thickness effect under the dry sliding condition are not completely suitable for the lubricated spindle of the cotton picker.…”
Section: At Varied Coating Thicknessmentioning
confidence: 92%
“…Optimization of the speed of rotation of the spindle and cleaning of its surface from the juices of plant fibers are devoted to the work [21][22][23][24][25]. The comparative analysis of the work performed showed that various graphical and analytical methods for studying the activity of the spindle were created.…”
Section: Introductionmentioning
confidence: 99%